„Vegetarian health resort” in Bojarów and its founder Konstanty Moes-Oskragiełło - Śmiechowicz, Anna (Perspektywa stołu, 2023)
In the second half of the nineteenth century, a vegetarian movement appeared in Poland, referring to the ideology of healing oppressed nations by renewing the spirit and body. Konstanty Moes-Oskragiełło was the propagator of this innovative idea under the partitions, who looked for a remedy for his deteriorated health in this idea. He was tenacious in promoting vegetarianism in Warsaw and Krakow, especially in Bojarów near Otwock. He created a spa there in 1883, where one of the methods of treatment was a diet devoid of meat products.